Using HOTS-Based Chemistry National Exam Questions to Map the Analytical Abilities of Senior High School Students - Johnsen Harta; Novena Tesalonika Rasuh; Angela Seriang (Journal of Science Learning, 2020)
High Order Thinking Skills (HOTS) are a significant part of the implementation of the 2013 Curriculum to develop student competencies in the 21st century. Not only in the context of learning are HOTS considered important. They contribute to the National Examination held in Indonesia, so careful preparation for this exam is needed. Chemistry has basic concepts that require students to search and find facts, understand concepts, apply them procedurally, and analyze deeply. This study aims to map the analysis ability of students in Yogyakarta in working on HOTS-based chemistry national exam questions. This research is a quantitative-qualitative descriptive study with XII year students at a senior high school in Yogyakarta. The instruments used in this study were HOTS essay questions, interview sheets, and questionnaire sheets, analyzed with the Rasch Model. The results show that the students' analysis ability was still relatively low, with person reliability values of 0.56 and 0.39, and a Cronbach's alpha of 0.78. The quality of the HOTS questions was very good, with item reliability 0.97 and 0.95. Not many students in the two senior high schools have good analysis ability, so students must be better trained to optimize their potential in HOTS-based chemistry learning.